Development of resources tu studoy geometry reusing materials - Sgreccia, Natalia Fátima (2024)
The Professorship in Mathematics of the National University of Rosario (Argentina) supports both educational research projects linked to teacher training, as well as university extension projects to articulate the work with schools in disadvantaged or vulnerable contexts through the use of physical didactic resources, in particular, for the teaching and learning of geometry. Access to these resources is not always direct, and limitations of various kinds are usually encountered. In this instance, some attempts to address such obstacles are documented, highlighting the intrinsic relationship between university extension and educational research for the improvement of educational proposals in geometry when teaching resources made by teachers and students themselves are used. As a peculiarity, it should be noted that for its elaboration it is sought to put into action the ecological 3Rs as a transversal contribution according to the Sustainable Development Goals.